Informe. 8. Conferencia Anual del Programa de Maíz. Medellín (Colombia), 24-26 Ago 1964. - Instituto Colombiano Agropecuario, Medellín (Colombia) (Instituto Colombiano Agropecuario, 1964)
Maíz-Zea mays